Livestock Building and Equipment Requirements - Langemeier, Larry N.; Murphy, James P. (My University, 1998)
This publication describes the livestock building and equipment requirements for producers.
MF940_1998_10
Keywords: MF940; Equipment and Structures; Livestock; Economics; MF